2022
DOI: 10.3389/fneur.2022.844841
|View full text |Cite
|
Sign up to set email alerts
|

A Set of Reliable Samples for the Study of Biomarkers for the Early Diagnosis of Parkinson's Disease

Abstract: BackgroundParkinson's disease (PD) is a progressive neurodegenerative disorder, diagnosed according to the clinical criteria that occur in already advanced stages of PD. The definition of biomarkers for the early diagnosis of PD represents a challenge that might improve treatment and avoid complications in this disease. Therefore, we propose a set of reliable samples for the identification of altered metabolites to find potential prognostic biomarkers for early PD.MethodsThis case–control study included plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…FFA may prevent the assembly of amyloid and tau filaments (Kruska and Reiser, 2011;Barracchia et al, 2020). FFAs, including palmitic acid, oleic acid, and stearic acid, have all been shown to have low concentrations in serum from PD patients in the preclinical stage (Havelund et al, 2017;Gonzalez-Riano et al, 2021), and were suggested as potential biomarkers of PD in a follow-up study (Havelund et al, 2017;Konjevod et al, 2022). Alpha-linolenic acid, classified as a polyunsaturated fatty acid, can inhibit 6-OHDA-induced dopaminergic neurodegeneration in worms (Shashikumar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…FFA may prevent the assembly of amyloid and tau filaments (Kruska and Reiser, 2011;Barracchia et al, 2020). FFAs, including palmitic acid, oleic acid, and stearic acid, have all been shown to have low concentrations in serum from PD patients in the preclinical stage (Havelund et al, 2017;Gonzalez-Riano et al, 2021), and were suggested as potential biomarkers of PD in a follow-up study (Havelund et al, 2017;Konjevod et al, 2022). Alpha-linolenic acid, classified as a polyunsaturated fatty acid, can inhibit 6-OHDA-induced dopaminergic neurodegeneration in worms (Shashikumar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…LC-QqQ/MS mobile phase 2 consisted of eluent A, identical to mobile phase 1, and eluent C made of ACN. The chromatographic method and the MS parameters were adapted from a method described in detail elsewhere. , Briefly, 20 μL of sample was injected into a thermostated (35 °C) Agilent RRHD Zorbax Extend C18 column (2.1 × 150 mm, 1.8 μm; Agilent Technologies, Waldbronn, Germany) equipped with an Agilent Zorbax Fast Extend C18 guard column (2.1 × 5 mm, 1.8 μm; Agilent Technologies, Waldbronn, Germany). The chromatographic separation was based on gradient elution using a binary pump at a flow rate of 0.25 mL·min –1 with a mobile phase made of 0% B from time 0–2.5 min, and then % B was progressively increased until 20% B at 7.5 min, up to 45% B at 13.0 min, and up to 99% B at 20.0 min, which was held until 24.0 min.…”
Section: Methodsmentioning
confidence: 99%
“…Although there have been recent advances in identifying potential biomarkers [24], including genetic [25,26] and neuroimaging techniques [11] that help in detecting PD, these are still in the early stages, and further work is needed in this direction. Further, it has also been recognized that a variety of nonmotor symptoms associated with PD may be observed years before the onset of motor symptoms and hence may be used as markers for detecting PPD [27].…”
Section: Introductionmentioning
confidence: 99%